Megadrought and collapse : from early agriculture to Angkor - Weiss, Harvey; Weiss, Harvey (Oxford University Press, 2017)
'Megadrought and Collapse' revises the global archaeological and historical record with nine case studies that describe and analyse decades to centuries long megadroughts, from the Pleistocene to the 15th century AD, and the societal collapses they caused. Each study is a definitive review of societal responses to natural climate change